The effect of pearlite morphology and crystallographic texture on environmentally assisted cracking failure. (August 2021) - de Carvalho Paes Loureiro, Rodrigo; Beres, Miloslav; Masoumi, Mohammad; Ferreira Gomes de Abreu, Hamilton
Highlights: Crack nucleated at surface pits and propagated in low angle grain boundaries. The refined microstructure prevents crack growth and can deflect crack propagation. The low cleavage resistance (0 0 1)//ND fiber texture facilitates the initiation and propagation of corrosion cracks. Abstract: Mechanism of failure by environmentally assisted cracking was extensively investigated in the present work to find the effect of pearlite morphology and crystallographic texture on crack nucleation and propagation sites. The macrotexture analysis revealed that (0 0 1) crystallographic texture components parallel to the normal direction was predominant in the investigated sample. Crack nucleated at surface pits and propagated in low angle grain boundaries. The refined microstructure prevents crack growth and can deflect crack propagation. High angle grain boundaries were found to suppress crack propagation. In the crack-free region (2 2 3) [1  1 ¯  0] and ( 1 ¯  1 1) [1  1 ¯  2] texture components were found. Therefore, the control of crystallographic orientation and engineering the grain boundary characteristics can effectively improve the environmentally assisted cracking resistance.